Use of Plant-Based Pore-Forming Agents in Ceramic Materials - Fey, Tobias; Hoffmann, Patrizia; Roland, Simon; Galic, Sascha (Cfi-Ceramic Forum International, 2024)
Porous ceramic materials can be synthesized by a variety of processes. In addition to the mechanical properties, the formation of the pores and the pore network is of crucial importance for a large number of applications. In particular, the use of natural cellulose-based pore-forming agents allows the porosity to be specifically adjusted from open-cell to closed-cell in the ceramic materials according to the applications, depending on the geometry. The advantage of these pore-forming materials lies on the one hand in the natural surface structuring, and on the other hand they have a much better CO2 balance. The potential of natural pore-forming agents and their influence on mechanical and thermal properties is demonstrated on the use of cellulose beads in different diameters and compositions for the preparation of biomorphous SiC-ceramic.
CRIS-Team Scopus Importer:2024-03-01
Keywords: bio-morphous ceramics; cellulose; natural pore former